Why break down centralized wage bargaining? - Timo Tyrväinen (Bank of Finland, 1989)
This paper reviews recent research on different modes of bargaining and their impact on economic performance. The aim is to examine whether a shift from a centralized bargaining procedure towards a less centralized mode would be favourable. The case is discussed in the special Scandinavian context where the relevant option is a shift from highly centralized wage bargaining to permanent industry-level bargaining. We wish to find out whether any of the existing research using a variety of models - both theoretical and empirical ones would support the proposed shift. We did not find any strong argument in favour of it.
URN:NBN:fi:bof-201908051344
Keywords: 330